This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Really good solution ! I like it !
Did the same thing!
Great way to solve this. Thanks.
Good solution.It is easy to understand.Upvoted!
Did the same thing!
We now that, if a , b ∈ R a 2 b 2 = ( a b ) 2 \ ( 6 0 + 3 7 ) 2 ( 6 0 − 3 7 ) 2 = ( ( 6 0 + 3 7 ) ( 6 0 − 3 7 ) ) 2 \ ( ( 6 0 ) 2 − ( 3 7 ) 2 ) 2 = ( 6 0 − 6 3 ) 2 ⟹ ( − 3 ) 2 = 9
WHAT, But look (\sqrt 60 + 3\sqrt7)^2 is 60 + 21 and the other equation is 60 - 21, then that is 81 * 39!
(a+b)^2 (a-b)^2=a^4+b^4-2ab So (√60)^4+(3√7)^4- 2(√60)^2(3√7)^2. =9
Did the same!
(a+b)^2 (a-b)^2
=a^4+b^4-2ab
so, (√60)^4+(3√7)^4- 2(√60)^2(3√7)^2. =9
((√60)²-3²(√7)²)² = (60-9*7)² = (-3)² = 9
i solve the problem using (a+b) 7 ( a-b) square formula
can i hv d solution.???
Problem Loading...
Note Loading...
Set Loading...
Reorder, we get:
( 6 0 − 3 7 ) ( 6 0 + 3 7 ) ( 6 0 − 3 7 ) ( 6 0 − 3 7 )
( ( 6 0 − 3 7 ) ( 6 0 + 3 7 ) ) 2
The expression above is a conjugate binomial to square.
⇒ ( 6 0 − 3 7 ) ( 6 0 + 3 7 ) = ( 6 0 ) 2 − ( 3 7 ) 2 = ( 6 0 − 6 3 ) = − 3
∴ ( ( 6 0 − 3 7 ) ( 6 0 + 3 7 ) ) 2 = ( − 3 ) 2 = 9